Exploring Hypertension Etiology and Patient Perspectives on Treatment in Ghana: A Qualitative Investigation - Fidelis Atibila; Gill Ten Hoor; Emmanuel Timmy Donkoh; Gerjo Kok (Hindawi Limited, 2024)
Background. Hypertension (HTN) is a growing public health concern affecting both economically developed and developing nations. In Ghana, HTN significantly impacts morbidity and mortality. Understanding the perspectives of HTN patients regarding its causes and treatment can enhance HTN management. This study explored patient perspectives on HTN in Ghana. Materials and Methods. An exploratory descriptive approach was used, in conducting in-depth interviews and focus group discussions. Purposeful sampling was used to select HTN patients, and thematic content analysis was employed for data analysis. Overall, 14 face-to-face interviews were carried out, and two FGDs were done. The FGD consisted of a total of 15 participants, 8 females and 7 males. Results. Four key perspectives emerged. These include (1) the description of HTN (patients defined HTN as excessive blood); (2) beliefs about the causes of HTN, some attributed HTN to witchcraft, considering it a curse from the gods and traditional medicine was seen as a potential cure; (3) health-seeking behavior, a notable discrepancy exists between patient and medical understandings of HTN, potentially causing healthcare delays; and (4) family support. Recommendation. The misunderstanding of HTN may hinder timely healthcare-seeking and medication adherence, exacerbating HTN-related complications. Addressing these beliefs through community health promotion programs is urgently needed.